Physiological changes across a sport season in a nine-time world-champion triathlete: a case report - Gonzalez-Custodio, A.; Crespo, C.; Timon, R.; Olcina, G. (Sports, 2025)
This case report analyses the physiological changes of a nine-time world champion triathlete over a competitive season. The triathlete, aged 34, resumed training after a 3-month injury-related break. The study monitored key physiological variables at three points: pre-season (PRE), base period (BASE), and peak performance (PEAK). The athlete trained an average of 25,000 m swimming, 400 km cycling, and 90 km running weekly. Incremental cycling tests were performed at each stage, measuring power output, oxygen uptake (VO2), ventilatory thresholds (VT1, VT2), muscle oxygen saturation (SmO2), heart rate, and lactate levels. Results showed significant improvements in relative power output (+37.2% at VT1), VO2 max (+12.6%), and body composition (body fat reduced from 10.43% to 7.33%). Heart rate and lactate concentration remained stable, while SmO2 showed a greater difference between VT2 and peak performance. The triathlete achieved top-10 finishes in all key events, including a win at the Ironman 70.3 World Championship. The findings suggest that elite triathletes can regain peak performance after injury through structured training, with improvements in ventilatory efficiency and body composition contributing to better competition results. This study provides valuable insights for coaches on the recovery and performance optimization of elite triathletes.